Phase retrieval of finite Blaschke projection. (24th June 2020) - Li, Youfa; Zhou, Chunxu
Abstract : Phase retrieval by Fourier measurements is a classical application in coherent diffraction imaging, and the modified Blaschke products (MBPs) are the generalization of linear Fourier atoms. Motivated by this, we investigate the phase retrieval modeled as to reconstruct P ( f ) = ∑ k = 0 ∞ ⟨ f, B a 0, a 1, …, a k ⟩ B a 0, a 1, …, a k by the intensity measurements | ⟨ f, B k 1 ⟩ |, | ⟨ f, B k 2 ⟩ |, | ⟨ f, B k 3 ⟩ | : k ≥ 1 , where f lies in Hardy space ℋ 2 ( D ) such that f ( a 0 )=0, B a 0, a 1, …, a k and B k i are all the finite MBPs. We establish the condition on B k i such that P ( f ) can be determined, up to a unimodular scalar, by the above measurements. A byproduct of our result is that the instantaneous frequency of the target can be exactly reconstructed by the above intensity measurements. Moreover, a recursive algorithm for the phase retrieval is established. Numerical simulations are conducted to verify our result.